(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2021)
Urinary incontinence (UI) is a prevalent clinical problem that affects women of all ages and from a wide range of cultures and ethnicities. UTI was described as the complaint of any involuntary urine leakage by the International Continence Society (ICS). An abnormality in the bladder or the sphincter system can cause urinary incontinence (UI). When it comes to the most prominent reasons of UI (stress, want and mixed), stress is the most prevalent. Urinary incontinence, pelvic floor, function of pelvic floor, muscles perineum, type of incontinence, and stress urinary incontinence are all discussed in this study.